Improving Channel Gain of 6G Communications Systems Supported by Intelligent Reflective Surface - Alsahlanee, Abbas Thajeel Rhaif; Al-Safi, Jehan Kadhim Shareef (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
The 6G wireless communication networks may use intelligent reflecting surfaces (IRS). It can enhance energy efficiency (EE). The IRS can enhance wireless communication by selectively reflecting incident signals in favorable directions. A potential method to improve the efficacy of wireless channels is to use a software-controlled metasurface that reflects signals when the direct transmission line from the source to the destination is insufficient. The IRS may redesign the environment to facilitate radio signal transmission. The decrease in channel gain in 6G communications networks using multiple reflective elements of the IRS is one of the challenges. This study seeks to propose a solution to enhance the channel gain and performance of the IRS in 6G communication systems. The research aimed to improve channel gain in assisted-IRS 6G communication systems by artificial intelligence algorithm (DS-PSO: dynamic and static particle swarm optimization). This study's technique enhances the effectiveness of aided-IRS communication methods. The simulation results of the optimized IRS model proposed in this paper show a significant improvement in channel gain compared to the results of previous studies.